Application of Behavioristic Learning Theory With The Qiro'ah Method In Al-Qur'an Memorization Learning - Amaliyah, Rizki; Wulansari, Mega (Jurnal Pengabdian Masyarakat, 2025)
Purpose: The purpose of this study is to explore the application of the Qiro’ah method in Qur’an memorization. This method emphasizes systematic recitation, mastery of correct tajwid (rules of Qur’anic recitation), and the use of supportive learning media to enhance the memorization process.   Method: A descriptive qualitative field approach was employed to examine the use of paper-based media in Qur’an memorization through the Qiro’ah method at the Tarbiyatul Ajyaal Darussalam Foundation.   Practical Applications: In practice, the Qiro’ah method is designed to help students understand and memorize Qur’anic verses more effectively, while also improving the quality of their recitation according to the rules of tajwid. The structured repetition and integration of learning tools support both retention and proper pronunciation.   Conclusion: Rooted in behaviorist theory, the Qiro’ah method proves effective in enhancing students’ motivation, consistency, and overall quality of Qur’an memorization. Its success is driven by systematic repetition and positive reinforcement. Despite challenges such as varying learning abilities and limited resources, the method remains a structured, engaging, and relevant approach to Qur’anic education.